Theorizing a Framework of Factors Influencing Business Performance: A Research Agenda for Muslim Women Entrepreneurs - UMMAH, MOHAMED ABDUL CADER SALFIYA; CHOY, CHONG SIONG; BEEVI, ATHAMBAWA SULAIHA (The journal of contemporary issues in business and government, 2021)
This study aims to comprehensively identify a framework of factors influencing the business performance of Muslim women entrepreneurs.The literature suggests thatthe factorscan be viewed from numerous theories related to the psychological, organisational context and environmental contextand contextualise them to analyse the association between the factors such as psychological characteristics, human capital, social capital, industrial factor andcultural factorwithin the boundary of Islamic traditions and values. Since the paper is conceptual in nature, a quantitative analysis incorporating the factors associated with business performance from the lens of different stakeholders such registered, unregistered Muslim women business owners, as well as managers will further reinforce its value.The comprehensive theoretical framework identified would provide significant insights to policy makers, trade associations and even Muslim women entrepreneurs themselves on what it takesto enhance their business performance.The comprehensive review is perhaps amongst the first to be carried out with theoretical, research and practical implications delineated for researchers and practitioners.